TINJAUAN YURIDIS TAMBAHAN PENGHASILAN PEGAWAI (TPP) ASN DI KABUPATEN BUTON - Darmawan Wiridin; Adli Bachmid (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2026)
This study aims to examine and analyze the legal basis, mechanism of the implementation of Additional Employee Income (TPP) for State Civil Apparatus (ASN) in Buton Regency from a Legal perspective. Additional Employee Income is one of the instruments of Regional Government policy to improve the welfare of State Civil Apparatus (ASN) while encouraging bureaucratic performance The research method used is normative, namely by using a statutory approach, a historical approach and a contextual approach, the author will refer to legal principles that can be found in scholarly regulations or other doctrines The results of the study indicate that although the provision of Additional Employee Income has been regulated through the Regent's Regulation, there are still weaknesses in the aspects of transparency and existing regulations. Therefore, a review and strengthening of regional regulations is needed so that the implementation of TPP can run well with the principle of legal.